2021
DOI: 10.3389/feart.2021.669885
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Tropical Trigger Hypothesis of Abrupt Climate Variability

Abstract: Dansgaard-Oeschger oscillations (DOs) are abrupt shifts in climate, which are dramatic temperature fluctuations observed in Greenland and recorded globally. These abrupt changes are associated with the slowing and shutting down of the Atlantic Meridional Overturning Circulation (AMOC), but despite their importance the driving forces of DOs are not fully understood. Here we assess the role of the AMOC during DOs, the Northern vs Southern Hemisphere control on AMOC, and the possibility of neotropical moisture as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 143 publications
(212 reference statements)
1
1
0
Order By: Relevance
“…Our ISM rainfall reconstructions show that monsoon rainfall remained strong throughout the MIS 5 interstadials despite progressive background climate cooling. This sustained monsoonal strength may have been conducive in facilitating high latitude ice sheet growth via moisture export to higher, cooler latitudes (Khodri et al, 2001), lending support to previous hypotheses invoking low-latitude controls on global climate changes (Ivanochko et al, 2005;Kaboth-Bahr et al, 2018;Kudrass et al, 2001;Oughton and Urrego, 2021). (Loulergue et al, 2008) h) Antarctic composite CO 2 ice-core record (Lüthi et al, 2008) i) EDC ice-core δD (Jouzel et al, 2007) j) Eccentricity (Laskar et al, 2004) k) Obliquity (Laskar et al, 2004) and l) 21st June NHSI at 65°N and 23°N (Laskar et al, 2004).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our ISM rainfall reconstructions show that monsoon rainfall remained strong throughout the MIS 5 interstadials despite progressive background climate cooling. This sustained monsoonal strength may have been conducive in facilitating high latitude ice sheet growth via moisture export to higher, cooler latitudes (Khodri et al, 2001), lending support to previous hypotheses invoking low-latitude controls on global climate changes (Ivanochko et al, 2005;Kaboth-Bahr et al, 2018;Kudrass et al, 2001;Oughton and Urrego, 2021). (Loulergue et al, 2008) h) Antarctic composite CO 2 ice-core record (Lüthi et al, 2008) i) EDC ice-core δD (Jouzel et al, 2007) j) Eccentricity (Laskar et al, 2004) k) Obliquity (Laskar et al, 2004) and l) 21st June NHSI at 65°N and 23°N (Laskar et al, 2004).…”
Section: Discussionsupporting
confidence: 73%
“…Despite the role of high-latitude climate processes in forcing internal climate perturbations (Broecker et al, 1992;Markle et al, 2017;Pedro et al, 2018), previous studies have revealed the importance of the lowlatitudes in determining and amplifying the subsequent global climate response through possible greenhouse gas feedbacks and global dissemination of heat and moisture (Cheng et al, 2020;Clement and Peterson, 2008;Ivanochko et al, 2005;Kudrass et al, 2001;Leduc et al, 2007;Nilsson-Kerr et al, 2019;Oughton and Urrego, 2021;Rohling et al, 2002;Sánchez Goñi et al, 2016). This has been attributed to the fact that the tropics are the primary absorber of the majority of incoming solar radiation (Chiang and Friedman, 2012).…”
Section: Influence Of Low-latitude Climate On Global Climatementioning
confidence: 99%